2021
DOI: 10.1101/2021.06.16.448433
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Reorganization of the Mitochondria-Organelle Interactome during Postnatal Development in Skeletal Muscle

Abstract: Cellular development requires the integrated assembly of intracellular structures into functionally specialized regions supporting overall cellular performance. However, it remains unclear how coordination of organelle interactions contributes to development of functional specificity across cell types. Here, we utilize a subcellular connectomics approach to define the cell-scale reorganization of the mitochondria-organelle interactome across postnatal development in skeletal muscle. We show that while mitochon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 59 publications
(105 reference statements)
1
10
0
Order By: Relevance
“…Consistent with our previous results (Bleck et al., 2018; Kim et al., 2021), almost every muscle mitochondrion was in contact with the SR regardless of cell type or subcellular region (Fig. 5), further indicating the critical importance of mitochondrial‐SR interactions in skeletal muscle.…”
Section: Resultssupporting
confidence: 92%
“…Consistent with our previous results (Bleck et al., 2018; Kim et al., 2021), almost every muscle mitochondrion was in contact with the SR regardless of cell type or subcellular region (Fig. 5), further indicating the critical importance of mitochondrial‐SR interactions in skeletal muscle.…”
Section: Resultssupporting
confidence: 92%
“…To further gain insight into mitochondrial morphological remodelling, Kim et al. (2024) analysed two abnormal mitochondrial morphologies described as markers of oxidative stress: (1) donut‐like mitochondria and (2) nanotubular mitochondria. The authors showed that donut and nanotubular formation are relatively rare at P1 and P14, and significantly increase in the P42 only for gastrocnemius.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, these experiments were done in gastrocnemius (glycolytic) and soleus (oxidative) muscle fibres from postnatal day (P)1, P14, and P42 male and female mice (C57BL6/N background). Kim et al (2024) demonstrated that mitochondrial network configuration is similar between glycolytic and oxidative muscle types at birth. There is an increase in mitochondrial volume and number in oxidative, but not glycolytic, fibres during development.…”
mentioning
confidence: 94%
“…The six muscle types with greater than 20% intrasarcomere CSA heterogeneity in Fig. 1 (mouse late postnatal and all three mature muscles, Drosophila leg, and human vastus lateralis) are all known to have large proportions of their mitochondrial networks which wrap perpendicularly around the sarcomere adjacent to the Z-disks, whereas the remaining five muscle types with less than 20% heterogeneity all have mitochondrial networks primarily oriented in parallel to the contractile apparatus 11,18,19,36,39,48,49 . Thus, we hypothesized that sarcomere structure is linked to mitochondrial network configuration.…”
Section: Sarcomere Shape Is Coordinated With Mitochondrial Locationmentioning
confidence: 99%
“…Image stacks within a volume were aligned using Atlas 5 software (Fibics Incorporated) and exported as TIFF files for analysis. Some raw FIB-SEM datasets were previously used to assess mitochondria-organelle interactions 11,48 , myofibril network connectivity 3,4 , and/or endothelial cell/myocyte interations 102 .…”
Section: Focused Ion Beam Scanning Electron Microscopymentioning
confidence: 99%